Interaksionisme Simbolik Michalowski dalam Memandang Bitcoin sebagai Kejahatan - Natasya Hana Rumondang (Jurnal Kriminologi Indonesia, 2019)
Ontologically, from a symbolic interactionist perspective, bitcoin can be viewed as a crime. This paper aims to explain how bitcoin viewed as a crime especially from Michalowski’s symbolic interactionism perspective. In the interactionist perspective, where society is plural and has different values from other groups, the definition of right or wrong depends on the plural and unique point of view of the community group. The difference in definition is the result of interactions and labels given by the community. Likewise, the view of crime can differ according to the interaction, definitions and labels given by society. In this case, Indonesian view bitcoin as a crime because of the perception that bitcoin is a virtual currency that is used to carry out illegal transactions.Keywords: bitcoin; crime; label; symbolic interactionism.